O ESTOICISMO E O CETICISMO: AS DUAS VIAS FILOSÓFICAS PARA A CONSTRUÇÃO DO PARADOXO ENTRE GRANDEZA E MISÉRIA EM BLAISE PASCAL - Rocha, Arlindo Nascimento (Último Andar, 2020)
Blaise Pascal is the philosopher of the paradox, because, for him, the truth is the meeting of opposites. In his anthropology, man is analyzed as a paradoxical being, at the same time big and small, weak and strong, big and miserable. These contradictions are present in all men, but most philosophers throughout the history of Western thought have seen only one side, that is, they have a unilateral and limited view of man. This article aims to analyze the two philosophical ways in which Pascal constructs the paradox between greatness and misery, as fundamental to the study and understanding of man. To this end, he especially supports two philosophers, Epiteto and Montaigne, showing that the ’truth’ of each philosophical chain operates as a disqualification from the ’truth’ of the other. But for Pascal, the true understanding of man, is in the meeting of these two contradictory dimensions, that is, paradoxical.